Can Vascularity Determine Degenerative Behavior of Uterine Fibroids? Huge Parasitic Uterine Fibroid Mass Mimicking an Ovarian Tumor (2017)
Uterine fibroids have been misdiagnosed for a range of conditions from ovarian to colonic or even retroperitoneal tumors. Apart from the effects of a known and diagnosed fibroid, misdiagnosed fibroids have their own implications for the patient which may include iatrogenic impaired reproductive capability and quality of life. An understanding of fibroid degenerations, especially atypical variants produced by associations between fibroid tumors and bowel or mesentery may help overcome this diagnostic dilemma and aid optimal care. Case Report: The authors report the case of a 30 year old nullipara, who had a huge cystic abdominal tumor with rich vascularity from a broad mesentery, causing complex degenerations and consequently an unusual anatomy. This fibroid tumor was misdiagnosed clinically and at radio-diagnosis for an ovarian malignancy, because of the nature of degenerations that had taken place. Conclusion: An understanding of such atypical degenerations may help to overcome diagnostic dilemma and aid optimal care.